INTEGRASI KEARIFAN LOCAL KE DALAM BAHAN AJAR FISIKA DI SEKOLAH - Zose Wirawan; M.Agus Martawijaya; Ahmad Yani (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to obtain valid, practical and effective student physics worksheets based on local wisdom. This study is a research and development study, while the development design uses Born and Gall. The research subjects were students of class XI IPA at SMA Negeri 7 Bone. The research data was collected through observation sheets and learning outcomes tests then analyzed descriptively. The learning tools developed in this study were student worksheets that were validated by experts and limited trials. The results of this study indicate the reliability value of 1. its practical value includes the implementation of learning, namely 1, the management of learning, namely 3.9 and good student response. The data on the effectiveness of this study were the test scores of student learning outcomes above 70. Based on the results of the study, it can be concluded that local wisdom-based physics worksheets were obtained for class XI IPA students of SMA Negeri 7 Bone that were valid, practical, and effective. It is further suggested that research be carried out with the development of different materials and modification of different eksperiment as a learning alternative for teachers in an effort to improve student learning outcomes.